Improving Social Studies Learning Outcomes by Using Picture and Projector Media - Komalasari, Rika; Nafsiah, Sifa; Nabillah Wondu, Tiara (Jurnal Primagraha, 2022)
This research aims to determine the results of social studies learning using picture media and a projector for class V students at SDN Catang 1, Serang Regency, Banten. The subjects of this research were 30 class V students at SDN Catang 1. The data collection techniques used were observation and interviews. The data analysis technique was carried out using a quantitative model to find out how important image media and projectors are for teachers and students in improving social studies learning outcomes by using image media and projectors in the learning process. Based on the data from the research conducted, it can be concluded that unique and interesting learning media are really needed by teachers and students. The presence of image media and projectors can make learning more fun, students are able to have open and broad knowledge, and do not get bored in the learning they do. . So, to improve student learning outcomes, especially in social studies subjects, it is very effective to use picture media and projectors because it can make it easier for students to follow the lesson clearly. Not only in social studies learning but for other learning it is also very much needed.